Intensity-modulated radiation therapy with concurrent chemotherapy for head and neck squamous cell carcinomas: toxicity assessment - Tuong, Pham Nguyen (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Intensity-modulated radiotherapy with concurrent chemotherapy attempt to maintain efficiency while limiting toxicity in the treatment of neck squamous cell carcinomas. Side effects of the therapy are both challenge during treatment such as treatment delay, increasing financial and hospitalization rate and also cause early and late toxicities, affects to patient performances and treatment outcomes. We aimed to assess acute and late toxicity in patients with head and neck squamous cell carcinoma (HNSCC) managed with concurrent chemoradiation therapy using intensity modulated radiation therapy (IMRT) technique. Methods: A prospective descriptive study of 120 patients suffering from non-metastatic HNSCC received Intensity-modulated radiotherapy concurrently with four to six cycles of cisplatin (30mg/m2/day/ weekly)from May 2017 to 2018 at Hue Central Hospital (Vietnam). The dose to the primary tumour and cervical lymph nodes totally taken was 70 Gy. Toxicities were gradedbased on the European Organization for Research and Treatment of Cancer (EORTC) and the Radiation Therapy Oncology Group (RTOG). Results: Acute toxicities were mainly at grade 1 with oral mucositis, dermatitis and nausea/vomiting. For late toxicities, grade 3 xerostomia accountings for 5.8%. Neck fibrosis and trismus were not at grade 3 to grade 4, grade 1 mandibular bone necrosis (3.4%) was found in 3 patients. Conclusions: Concurrent chemoradiation therapy with IMRT demonstrated a well-tolerated regime with manageable toxicities. Keywords: Intensity-modulated radiation, Chemotherapy, Toxicity